Македонські традиційні жіночі головні прикраси – функція і значення - Ристовська Пиличкова, Я. (Народна творчість та етнографія, 2009)
From the stated above we can conclude that these decorative elements are used for the head, particularly lesa and kocel, which are found on women’s and especially brides costume from some parts of Macedonia. They consist of series of esthetical, functional and magical-ritual elements that clearly associate them with ancient archaic cults of fertility. All these speaks of unavoidable influences and trails left from ancient pagan ritual forms and their sincretization in folklore of Slovenes nations, connected with cult of fertility and cyclic renovation of natural cosmic forces.